2015
DOI: 10.1016/j.taap.2015.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inorganic arsenic exposure in vitro induces a cancer cell phenotype in human peripheral lung epithelial cells

Abstract: Inorganic arsenic is a human lung carcinogen. We studied the ability of chronic inorganic arsenic (2 μM; as sodium arsenite) exposure to induce a cancer phenotype in the immortalized, non-tumorigenic human lung peripheral epithelial cell line, HPL-1D. After 38 weeks of continuous arsenic exposure, secreted matrix metalloproteinase-2 (MMP2) activity increased to over 200% of control, levels linked to arsenic-induced cancer phenotypes in other cell lines. The invasive capacity of these chronic arsenic-treated lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 60 publications
(115 reference statements)
3
17
0
Order By: Relevance
“…Thus, KRAS activation in the transformed RWPE-1 cells is dependent on the carcinogen. Our current findings are consistent with other studies which report KRAS activation in Cd- and arsenic-transformed human lung cells, 17,26 suggesting KRAS activation appears to be an important event for both of these inorganic carcinogens. Interestingly, the lung is a human target tissue for both Cd and arsenic.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, KRAS activation in the transformed RWPE-1 cells is dependent on the carcinogen. Our current findings are consistent with other studies which report KRAS activation in Cd- and arsenic-transformed human lung cells, 17,26 suggesting KRAS activation appears to be an important event for both of these inorganic carcinogens. Interestingly, the lung is a human target tissue for both Cd and arsenic.…”
Section: Discussionsupporting
confidence: 93%
“…These special properties include binding of up to 7 Zn 2+ and Cd 2+ , forming two metal‐thiolate clustered domains (the α and β‐domains) that are joined by a short linker sequence . While the biological function(s) of this family of proteins are still debated, it is generally agreed that their functions are connected with zinc and copper homeostasis, redox signalling, and toxic metal sequestration . Despite these many proposed functions, and their capacity to bind so many metals, MTs are surprisingly small, flexible proteins that lack optically active structural features.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 While the biological function(s) of this family of proteins are still debated, it is generally agreed that their functions are connected with zinc and copper homeostasis, [4][5][6][7] redox signalling, [8][9][10] and toxic metal sequestration. [11][12][13][14][15] Despite these many proposed functions, and their capacity to bind so many metals, 16,17 MTs are surprisingly small, flexible proteins that lack optically active structural features. This lack of formal secondary and tertiary structure in the absence of bound metal ions precludes traditional structural analysis via spectroscopic methods.…”
Section: Introductionmentioning
confidence: 99%
“…Since several studies have shown that arsenic-induced malignant transformation is frequently accompanied by cellular morphology changes resembling EMT (Eckstein et al 2017;Person et al 2015;Wang et al 2013), we investigated EMT markers after longterm arsenic exposure. Indeed, we observed loss of keratin 14 and ZO-1 together with an increase in spheroid formation capability in all chronically treated cells.…”
Section: Discussionmentioning
confidence: 99%